2016 IEEE International Conference on Communications Workshops (ICC) 2016
DOI: 10.1109/iccw.2016.7503786
|View full text |Cite
|
Sign up to set email alerts
|

Multi-connectivity functional architectures in 5G

Abstract: Future mobile networks need to fulfill stringent requirements on data rates, reliability, and availability. In order to satisfy these requirements, heterogeneous radio access technologies and deployments need to be used. To make efficient use of these technologies, multi-connectivity has been proposed to connect to multiple different technologies simultaneously. In this paper, we discuss different options to connect to multiple radio access points. Each of these options is further detailed, novel functionality… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
2

Relationship

3
6

Authors

Journals

citations
Cited by 71 publications
(49 citation statements)
references
References 5 publications
1
48
0
Order By: Relevance
“…Nevertheless, the common MAC approach offers the advantage of fast information exchange between the different multi-connectivity legs. This facilitates coordinated scheduling, interference mitigation, and other schemes related to MAC scheduling [14].…”
Section: Multi-connectivity (Mc)mentioning
confidence: 99%
“…Nevertheless, the common MAC approach offers the advantage of fast information exchange between the different multi-connectivity legs. This facilitates coordinated scheduling, interference mitigation, and other schemes related to MAC scheduling [14].…”
Section: Multi-connectivity (Mc)mentioning
confidence: 99%
“…Next, we can directly conclude (20) from (23) by substituting f (θ) = sin(θ − θ) in (23). For α = 2, which is a typical value for the path loss exponent for LoS mmW links, (20) can be simplified into (21) by taking the integration by parts in (20).…”
Section: A Average Achievable Rate For Cachingmentioning
confidence: 99%
“…Multi-connectivity in literature: Although a relatively recent topic, multi-connectivity has appeared in a number of relevant publications so far. An extensive view of the underlying architecture supporting multi-connectivity across different RATs is provided in [4], [5], where it was concluded that such multi-RAT architecture should employ common high layer protocol as well as centralized radio resource management. Specific characteristics and requirements of multi-connectivity when applied to millimeter-Wavelength (mmW) networks are provided in [6], [7].…”
Section: A the Concept Of Multi-connectivitymentioning
confidence: 99%